2016
DOI: 10.1002/ppp.1902
|View full text |Cite
|
Sign up to set email alerts
|

Over-Winter Channel Bed Temperature Regimes Generated by Contrasting Snow Accumulation in a High Arctic River

Abstract: We report experimental results of near-surface winter temperatures along and adjacent to the channel bed of a High Arctic river on Melville Island, Canada. Temperature loggers 5 cm below the ground surface in areas where the terrain suggests varying snow accumulation patterns revealed that the maximum winter difference between air and near-surface temperatures ranged from 0 to +30°C during the winter of 2012-13, and that shallow near-surface freezing conditions were delayed for up to 21 days in some locations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 33 publications
1
16
1
Order By: Relevance
“…25 However, these processes remain poorly understood in the High Arctic, and recent channel temperature work at CBAWO has demonstrated that the accumulation of thick winter snowpack due to wind redistribution of snow can maintain highly protected channel thermal settings. Bonnaventure et al 27 noted that the influence of snow on winter heat loss and freeze dates was substantial, and in one instance where several meters of snow accumulated, shallow channel bed temperatures were 30 C warmer than ambient air temperatures. They noted autumn freezeup was delayed by up to 21 days due to channel snow accumulation, but that spring thaw was relatively consistent due to meltwater reaching the channel in a short interval through the channel system.…”
Section: Climate Change Impacts On Hydrological Responsementioning
confidence: 99%
See 1 more Smart Citation
“…25 However, these processes remain poorly understood in the High Arctic, and recent channel temperature work at CBAWO has demonstrated that the accumulation of thick winter snowpack due to wind redistribution of snow can maintain highly protected channel thermal settings. Bonnaventure et al 27 noted that the influence of snow on winter heat loss and freeze dates was substantial, and in one instance where several meters of snow accumulated, shallow channel bed temperatures were 30 C warmer than ambient air temperatures. They noted autumn freezeup was delayed by up to 21 days due to channel snow accumulation, but that spring thaw was relatively consistent due to meltwater reaching the channel in a short interval through the channel system.…”
Section: Climate Change Impacts On Hydrological Responsementioning
confidence: 99%
“…They noted that some channel reaches remained above −10°C for up to 117 additional days, further suggesting an ameliorated channel thermal environment for biogeochemical cycling. What remains unclear is the extent to which this channel thermal heterogeneity due to snow cover affects seasonal thaw depth and hyporheic flow development, and to what extent and duration thawed zones exist at depth in the channel system due to snow affects biogeochemical processes and fluxes …”
Section: Introductionmentioning
confidence: 99%
“…When low levels of precipitation are typical, local snow accumulation patterns are relatively consistent in the High Arctic from year-to-year, accumulating in topographically controlled locations (Yang and Woo, 1999;Bonnaventure et al, 2016). Snow depth records obtained from the weather stations at BH3, BH4, and BH5 for the period 2002-2006 are shown in Figure 4.…”
Section: Snow Cover Effectsmentioning
confidence: 99%
“…The lack of a prolonged period of ground temperature near 0 °C during active layer freeze-back (zero curtain) and relatively small to nonexistent thermal offset (i.e., difference between surface temperature and TTOP) are also indicative of fairly dry conditions (Taylor et al, 1982;Throop, 2010). With little moisture existing in the near surface a thermal conductivity ratio (r k ) value of one was utilized, which is similar to that used in other dry High Arctic environments (e.g., Bonnaventure et al, 2016). To consider just the inversion effects, an n f value of one was used to represent the lack of snow cover, with variable values of n f (based on observed air and ground surface temperatures) used to examine the effects of variable snow cover.…”
Section: Permafrost Thermal Heterogeneitymentioning
confidence: 99%
See 1 more Smart Citation